2017
DOI: 10.1155/2017/9348159
|View full text |Cite
|
Sign up to set email alerts
|

Mental and Reproductive Health Correlates of Academic Performance among Debre Berhan University Female Students, Ethiopia: The Case of Premenstrual Dysphoric Disorder

Abstract: Background Globally 3 to 8% of reproductive age women are suffering from premenstrual dysphoric disorder (PMDD). Several mental and reproductive health-related factors cause low academic achievement during university education. However, limited data exist in Ethiopia. The aim of the study was to investigate mental and reproductive health correlates of academic performance. Methods Institution based cross-sectional study was conducted with 667 Debre Berhan University female students from April to June 2015. Aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
8
3
Order By: Relevance
“…In the current study, the most commonly reported symptoms were lethargy; easily fatigability or marked lack of energy (63.5%); decreased interest in usual activities (58.5%); and physical symptoms such as breast tenderness or swelling, joint or muscle pain, and a sensation of ‘bloating’ and weight gain (56.5%). It was consistent with the study findings indicated in Mekelle University, Ethiopia, 12 31 44 and in Iran 42 and India. 45 Sense of being overwhelmed or out of control 17.1%, marked depressed mood, feeling of hopelessness or self-deprecating thoughts 27.2% were the least prevalent symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, the most commonly reported symptoms were lethargy; easily fatigability or marked lack of energy (63.5%); decreased interest in usual activities (58.5%); and physical symptoms such as breast tenderness or swelling, joint or muscle pain, and a sensation of ‘bloating’ and weight gain (56.5%). It was consistent with the study findings indicated in Mekelle University, Ethiopia, 12 31 44 and in Iran 42 and India. 45 Sense of being overwhelmed or out of control 17.1%, marked depressed mood, feeling of hopelessness or self-deprecating thoughts 27.2% were the least prevalent symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…The possible variation for this difference could be due to tool difference (Premenstrual Assessment Scale (PAS)), sample size (1379), socio-cultural, sampling technique and being young, as the contribution of mixed psychobiological signs and symptoms of premenstrual problem in Iran. On the other hand, the magnitude of PMDD in this study was higher than the studies conducted in other areas of Ethiopia at 13.8%, 12 26.8% 13 and 27%; 44 Jordan 7.7%; 36 and India 3.7% and 12.22%. 45 46 In the studies conducted in the other areas of Ethiopia, the prevalence of PMDD was lower than the current study.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…All studies included in this analysis were conducted using a cross-sectional study design [7,8,[16][17][18][19][20][21][22]. For eight of these studies, the premenstrual syndrome scoring tool of Diagnostic and Statistical Manual of Mental Disorders, 4th Ed (DMS IV) was used while the American College of Obstetricians and Gynecologists (ACOG) was used for the remaining one study [7].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A wide range of prevalence rates was reported in the nine studies [7,8,[16][17][18][19][20][21][22]. The lowest prevalence of PMS, 27.00% (95% CI: 21.41, 32.59) was reported in a study among Jimma University female students [16].…”
Section: Prevalence Of Premenstrual Syndromementioning
confidence: 99%